HUBUNGAN GAYA HIDUP DENGAN KEJADIAN PREEKLAMSIA PADA IBU HAMIL - Yanti, Aditya Dwi; Novia, Resi; Amru, Desi Ernita (Ensiklopedia of Journal, 2026)
Preeclampsia, one of the complications that occurs in pregnant women, is characterized by increased blood pressure and the presence of protein in the urine of pregnant women. Preeclampsia attacked 363 pregnant women in the city of Batam. Preeclampsia is caused by several factors, one of which is lifestyle. The aim of this research is to determine the relationship between lifestyle and the incidence of preeclampsia in pregnant. This research design uses case control. Respondents in this study were 18 cases and 18 controls. Sampling used purposive sampling technique. The Chi-Square test results show (P-value 0.008 OR 9.100) so that Ho is rejected and Ha is accepted. So it can be concluded that there is a relationship between lifestyle and the incidence of preeclampsia in pregnant women and with an OR value of 9.100, which means that pregnant women with an unhealthy lifestyle are 9.100 times more likely to experience preeclampsia than those with a poor lifestyle. live well. The results of this research are expected for pregnant women to adopt a good lifestyle to prevent preeclampsia and for health workers to improve the quality of health services by providing education or counseling to pregnant women to prevent preeclampsia Keywords: Lifestyle, Preeclampsia, Pregnant Women